2022
DOI: 10.3390/nu14020396
|View full text |Cite
|
Sign up to set email alerts
|

Marine Oil from C. finmarchicus Enhances Glucose Homeostasis and Liver Insulin Resistance in Obese Prediabetic Individuals

Abstract: The intermediate state between normal glucose tolerance and overt type 2 diabetes mellitus is associated with micro- and macrovascular diseases, requiring safe and cost-effective treatment measures interventions. A novel source of LC n-3 FAs is Calanus finmarchicus Oil, which showed promising effects on glucose homeostasis in preclinical studies due to anti-obesity effects and/or anti-inflammatory properties. In total, 43 obese patients (BMI: 31.7 ± 5.2 kg/m2) were allocated in the following two groups: (1) Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Only a few studies have been taken out that investigated the bioavailability of CO. Cook et al focused on the short‐term bioavailability of CO in plasma over 72 h (Cook et al, 2016). Two long‐term studies focused on the metabolic effects of CO, but also found that CO, supplemented over 12‐weeks, significantly increased the O3I (Burhop et al, 2022; Wasserfurth et al, 2020). The present study also aimed to investigate the influence of CO on the O3I, but in comparison to conventional n3 PUFA sources such as FO and KO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have been taken out that investigated the bioavailability of CO. Cook et al focused on the short‐term bioavailability of CO in plasma over 72 h (Cook et al, 2016). Two long‐term studies focused on the metabolic effects of CO, but also found that CO, supplemented over 12‐weeks, significantly increased the O3I (Burhop et al, 2022; Wasserfurth et al, 2020). The present study also aimed to investigate the influence of CO on the O3I, but in comparison to conventional n3 PUFA sources such as FO and KO.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the short-term bioavailability (72 h) of CO, and thus, WE-bound fatty acids, is comparable to that of EE-bound n3 PUFA from fish oil (Cook et al, 2016). The bioavailability of n3 PUFA from CO over 12 weeks has also been confirmed in recent studies (Burhop et al, 2022;Wasserfurth et al, 2020). However, comparative bioavailability studies with CO and other conventional n3 PUFA oils are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, preclinical findings have indicated antioxidant and anti-inflammatory efficacy of this copepod oil beyond that provided by EPA and DHA ( Schots et al, 2020 ), which are presumably due to fatty acid conversion from their corresponding fatty alcohols ( Gasmi et al, 2020 ). In this respect, notable is the discovery of major effectiveness of COil on glucose metabolism and insulin resistance in obese patients in which the different lipid components of COil may have potential as nutraceuticals for reducing obesity and obesity-related metabolic disorders ( Burhop et al, 2022 ). In mouse models of obesity, COil supplementation in addition to efficiently counteract obesity-induced alterations, has been also demonstrated to exert anti-hypertensive effects and to improve post-ischemic cardiac recovery ( Salma et al, 2016 ; Jansen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%